Additional value of the red blood cell distribution width to the Mehran risk score for predicting contrast-induced acute kidney injury in patients with ST-elevation acute myocardial infarction. Issue 1 (July 2015) - Mizuno, Atsushi; Ohde, Sachiko; Nishizaki, Yuji; Komatsu, Yasuhiro; Niwa, Koichiro
Abstract Background Contrast-induced acute kidney injury (CI-AKI) after percutaneous coronary intervention in patients with ST-elevation myocardial infarction (STEMI) is a common complication associated with worse outcome. Considering the prognostic predictive value of the red cell distribution width (RDW), we aimed to measure the usefulness of RDW for predicting CI-AKI. Methods All consecutive STEMI patients without hemodialysis from June 2011 to September 2013 admitted to St. Luke's International Hospital were enrolled. We performed primary percutaneous coronary intervention in all patients. CI-AKI was defined as a >25% increase or an absolute increase in serum creatinine of 0.5 mg/dl within 3 days after percutaneous coronary intervention. The potential additional predictive value of RDW with the Mehran risk score (MRS) on admission was estimated. Results A total of 102 patients (78.4% males) were analyzed – 10 of the 102 (10%) STEMI patients developed CI-AKI. Multivariate analysis showed that RDW was an independent variable predicting CI-AKI in these patients [odds ratio, 2.029; 95% confidence interval (95% CI), 1.029–3.999; p = 0.041]. The areas under the receiver operating characteristic curves for MRS only, RDW only, and the combined model (MRS and RDW) for the prediction of CI-AKI were 0.806 (95% CI, 0.696–0.917), 0.719 (95% CI, 0.536–0.902), and 0.846 (95% CI, 0.744–0.949), respectively. Conclusion We showed the potential predictive ability of RDW, only if used with MRS, for CI-AKI in STEMI patients. Further evaluation of RDW for predicting CI-AKI in patients with STEMI is needed.